Genetics of canine diabetes mellitus part 2: Current understanding and future directions. (April 2021) - Denyer, Alice L.; Catchpole, Brian; Davison, Lucy J.; ,
Highlights: Large scale genetic studies have been key in human diabetes mellitus (DM) research. Genetic studies in canine DM have primarily used a candidate gene approach, to date. Recent technological advances have great potential for canine DM genetic research. The population structure of dogs is important for study of complex genetic diseases. Abstract: Part 1 of this 2-part review outlined the importance of disease classification in diabetes genetic studies, as well as the ways in which genetic variants may contribute to risk of a complex disease within an individual, or within a particular group of individuals. Part 2, presented here, describes in more detail our current understanding of the genetics of canine diabetes mellitus compared to our knowledge of the human disease. Ongoing work to improve our knowledge, using new technologies, is also introduced.